Respons Komunitas Muslim Indonesia terhadap Wabah COVID-19: The Responses of Indonesian Muslim Religious Community to the COVID-19 Outbreak - Ahmad Taufik (Jurnal Bimas Islam, 2021)
Indonesian religious leaders played a key role in the COVID-19 pandemic because their decisions and views are listened to by a vast majority in the Muslim community. This study focuses on the reactions and views of mainstream Islamic organizations such as Nahdlatul Ulama, Muhammadiyah, Majelis Ulama Indonesia (MUI), Jamaah Tabligh and Front Pembela Islam (FPI) and some Muslim fugues such as Ustadz Abdul Somad, and Kyai Najih in Indonesia to address COVID-19. This paper found that the response of some Muslim communities to Covid-19 has not yet completely complied with the Indonesian government's guidelines. During the Covid-19 pandemic, some religious leaders conducted and promoted worship gatherings. This is demonstrated by the reaction showing the pros and cons of Muslim societies and also appears to be resistant to the policies set. Second, mainstream Islamic organizations such as NU, MU, and MUI have adopted a logical, realistic approach in asking their adherents to comply with the social distance guidelines of the authorities. However, conspiracy theories by some Islamic teachers have complicated the situation. The third, in the early emergence of Covid-19 in Indonesia (January and February), the responses of religious leaders are fragmented and questioned, but steadily, along with COVID-19 cases increasingly spreading in Indonesia, some Islamic organizations (such as MUI, Muhammadiyah, and NU) and Islamic figures (Abdul Somad, Kyai Najih , and Nasaruddin Umar) are working hard hand in hand in compliance with the guidelines.